(untitled) (Prilozi za orijentalnu filologiju, 2017)
The present paper is the critical edition and translation, as well as the historical, literary-historical and philological commentary on the rebuking poem (tevbīxnāme) written by the Bosnian poet Fidai-bey and dedicated to the behaviour of the Bosniaks in the battle near Senta in September 11th, 1697. The poet himself particip-ated in that battle. The poem was recorded in the collection Tliffx-i Envefi by Muhamed Enveri-effendi Kadić (Sarajevo 1855 - Sarajevo 1931). This Collection is now preserved in the Gazi Husrev bey's Library in Sarajevo. The researches in this document make the following facts evident: . 1. Fidai-bey's poe m is :"the important historical source concerning the battle near Senta in Sept Qer l11h, 1697. lt confirms indirectly that the assertions of Luka Barka',•ihe envoy of Dubrovnik in the Porte, that the whole cavalry was saved in the battle, are acceptable, if not even completely correct. 2. This rebuking poem is the excelknt source for the history of Ottoman and B snian sfahiyan's mentality: The preoccupations and views of a man belonging to the Ottoman provincial middle class speak through this poem. 3. lt is also the unique literary and important linguistic document. It falls into the categories of satirical poetry and autobiographica1 narrative, which are very rare in Ottoman literature, while by its autosatirical dimension it is the exception in the history of that literature. As for the linguistic characteristics, '.this poem bears witness to the specific features of the Ottoman language spoken by the educated people from Bosnia. The language of the diwan poetry, simplier one, so called Vulgar Ottoman is here intertwined with the Bosnian dialect of the Ottoman language (Bosna lehčesi). 4. We made the hypothesis that the poet Fidai-bey was the founder of the dynasty of Zvornik's kapudans and sancakbeys Fidahić. If our assumption is correct, then it is the step ahead for understanding the cultural milieu of Bosnia in the Ottoman period, and it also goes in favour of the thesys that the literature in Oriental languages was not exclusively preoccupation of the ulema (scholars in theology).